Esperienze LGBTQ+ nel teatro musicale italiano contemporaneo: Interviste a Marco Benetti, Fabrizio Funari, ed Emily De Salve - Palma, Daniele (Mimesis Journal, 2021)
The current Italian landscape of performing arts shows the almost complete absence of a programmatically queer music theatre. Nevertheless, within this frame some recent experiences have been thematising LGBTQ+ ideas, characters and figures. In particular, in the present article I investigate La Traviata Norma (Conservatorio di Como, 2018, and Milano, Teatro Elfo Puccini, 2019) and Tredici Secondi, o Un bipede implume ma con unghie piatte(Venezia, Biennale College Musica, 2019). Direct voice is given to the composer Marco Benetti, the librettist Fabrizio Funari, and the transgender baritone Emily De Salve, who contributed to the creation of these two works. As a result, multiple perspectives emerge on how a queer gaze could be articulated in today’s music theater , also in light of the shared issue of constructing one’s own artistic persona within the cultural constraints of the operatic production system.